Life cycle assessment of alternatives for recycling abroad alkaline batteries from Portugal - Susana Xará (2014)
The European legislation establishes collection rates and states that all identifiable batteries must undergo treatment and recycling. Due to the inexistence in Portugal of recycling plants for alkaline batteries, those collected there have been sent to Austria and France, and currently, it is pondered to send them to Spain. This study aims to know the potential environmental impacts associated with the management of spent domestic alkaline batteries from collection in continental Portugal to recycling abroad. Three alternative recycling processes are considered: in Austria (A), France (F) and Spain (S). The system in study, from battery collection in continental Portugal to recycling abroad, includes complementary processes necessary for this circuit such as the production of boxes for battery collection and/or transportation and, for easiness of analysis and interpretation, is divided into: (i) container manufacture; (ii) distribution of empty containers; (iii) battery collection and sorting; (iv) international transport for the recycling; and (v) battery recycling. Recovered materials were also quantified. The LCA methodology and the method of impact assessment Eco-indicator 99, Hierarchist version, with two options, with and without inclusion of long-term emissions, were used. This method considers three damage categories: human health, ecosystem quality and resources, which group 11 impact categories. For ecosystem quality, there is a preponderance of the impact of recycling processes F and S regarding all other processes and, in particular, regarding recycling process A. After these, the container production impact is the most significant followed by the transport to Austria. For human health, there is a preponderance of the impact of recycling process S followed by the impact of F, and then of the transport to Austria and, only after, the impact of recycling process A. For resources, process S impact is higher than the one of A and this is higher than system F. The transport shows an expectable impact (highest for Austria, lowest for Spain), but for Austria and for France, it is higher than the impact of the recycling process itself. System F is the most negative in terms of ecosystem quality and S is the worst in terms of human health. In these two damage categories, system A is the best but the worst in the damage category of resources, where F is the best system. If the recovered materials are considered in this balance, the environmental advantage of system A is clear.